PUBLIC EXPENDITURE ON HEALTH AND EDUCATION AS A GROWTH STRATEGY: INSIGHTS FOR BUSINESS AND POLICY IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
Public spending on health and education significantly influences economic growth in Pakistan. Health expenditure has remained between 0.5% and 0.9% of GDP from 2000 to 2023, far below the WHO-recommended 5%. Life expectancy increased from 61 years in 2000 to 67.9 years in 2023, while infant mortality declined from 80 to 54.2 per 1,000 live births. Immunization coverage reached nearly 80%, yet healthcare accessibility disparities persist between urban and rural areas. Non-communicable diseases like diabetes and cardiovascular disorders are on the rise, adding pressure to the already underfunded healthcare system. Education spending has averaged around 2% of GDP, despite repeated government commitments to increase investment. The literacy rate rose from 48.7% in 2000 to 62.3% in 2023, but challenges remain, including high dropout rates, insufficient school infrastructure, and skill mismatches in the labor market. Higher education enrollment has improved, yet a lack of vocational training and curriculum modernization limits education’s contribution to economic progress. This study examines the link between public health and education expenditure and economic growth in Pakistan from 1992 to 2023 using the ARDL Co-integration technique. Findings reveal that health spending significantly enhances workforce productivity and economic performance, while education expenditure, though showing a positive trend, remains statistically insignificant due to quality and accessibility challenges. Exports serve as a major driver of economic expansion, underlining the importance of trade in sustaining growth. Pakistan must adopt a strategic approach to public investment. Increased healthcare spending can improve labor efficiency, while educational reforms should focus on aligning skills with market needs. Strengthening export policies will further accelerate economic development. Prioritizing these areas is crucial for long-term stability and progress. It looks like you're looking for key terms related to Public Expenditure on Health and Education as a Growth Strategy: Insights for Business and Policy in Pakistan. Here are some key words and phrases that might be useful.